Teacher Performance in State Madrasah Aliyah: Classroom Management, Work Motivation, and Assessment Competence - Enung Nugraha; Encep Syarifudin; Muhammad Fauzi; Siti Patimah; Aan Ansori; Amin Hidayat (SCAD Independent, 2026)
Teacher performance has become a central issue in improving the quality of Islamic secondary education, particularly within the Madrasah Aliyah state that faces increasing demands for educational accountability, instructional effectiveness, and professional teacher competency. This study examined the influence of classroom management ability, work motivation, and cognitive assessment competence on teacher performance in urban-based state Madrasah Aliyah in Banten Province, Indonesia. Using an explanatory quantitative design with a cross-sectional survey approach, data were collected from 313 teachers selected through simple random sampling from a population of 529 teachers. Data were analysed using descriptive statistics and multiple linear regression. The findings revealed that classroom management ability, work motivation, and cognitive assessment competence had positive and significant effects on teacher performance, both partially and simultaneously. Among these variables, cognitive assessment competence emerged as the strongest predictor of teacher performance. The study further demonstrated that teacher performance in faith-based education systems should be understood as a multidimensional construct shaped by the interaction among pedagogical competence, professional motivation, and assessment literacy. This research contributes to the development of competency-based teacher evaluation models within Islamic secondary education and strengthens the global discourse on teacher professionalism in faith-based education systems.